1976
DOI: 10.1159/000144633
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative innervation of the esophagus

Abstract: The osmium tetroxide-zinc iodide technique has been applied to the study of the tela submucosa and tunica muscularis in the esophagus of the cat and the rhesus monkey. Other than the classical terminal vegetative formation, three types of endings were found, classified as perifascicular, free and intramuscular. The comparative results between cat and rhesus monkey show differences in the distribution and number of such endings. A sensory functional significance is proposed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Although these studies have suggested a role of mucosal receptors in gastric emptying, by detecting food particle size, and in the regulation of the vomiting vagal reflex (Becker and Kelly, 1983;Andrews and Wood, 1988;Kentish et al, 2015), none have directly shown the physiological role of mucosal afferents in vivo. Furthermore, mucosal afferents possess a diversity of morphological substructures and the ability to detect different types of tactile mechanical stimuli (Rodrigo et al, 1970(Rodrigo et al, , 1975aPedrosa et al, 1976;Wank and Neuhuber, 2001), similar to the cutaneous touch receptor characteristics (Abraira and Ginty, 2013). While this suggests that true mucosal mechanoreceptors may act as touch receptors for the viscera, the presence of polymodal (i.e., detect chemical and thermal stimuli) vagal afferent populations may contradict this premise (Iggo, 1955;Clarke and Davison, 1978;Jänig, 1996;Lennerz et al, 2007).…”
Section: Mucosal Receptorsmentioning
confidence: 99%
“…Although these studies have suggested a role of mucosal receptors in gastric emptying, by detecting food particle size, and in the regulation of the vomiting vagal reflex (Becker and Kelly, 1983;Andrews and Wood, 1988;Kentish et al, 2015), none have directly shown the physiological role of mucosal afferents in vivo. Furthermore, mucosal afferents possess a diversity of morphological substructures and the ability to detect different types of tactile mechanical stimuli (Rodrigo et al, 1970(Rodrigo et al, , 1975aPedrosa et al, 1976;Wank and Neuhuber, 2001), similar to the cutaneous touch receptor characteristics (Abraira and Ginty, 2013). While this suggests that true mucosal mechanoreceptors may act as touch receptors for the viscera, the presence of polymodal (i.e., detect chemical and thermal stimuli) vagal afferent populations may contradict this premise (Iggo, 1955;Clarke and Davison, 1978;Jänig, 1996;Lennerz et al, 2007).…”
Section: Mucosal Receptorsmentioning
confidence: 99%